PELATIHAN MENDELEY 2022 BERSAMA NGAMPOOZ - Teja Endra Eng Tju; Julaiha Probo Anggraini (Universitas Pelita Harapan, 2022)
In 2022 Mendeley launched the Mendeley Reference Manager so it is necessary to conduct training as a form of community service that aims to improve the literacy ability of scientific papers in terms of searching and citation of a library. The activity partners with Ngampooz so that it can be well organized starting from participant registration to the submission of materials and participant certificates through the Ngampooz application. The main activity is training carried out online with the Zoom application and participants practice directly for each part of the material on their respective computers. The profile of participants consists of students, students, lecturers, engineers, and employees from various institutions in Jakarta and its surroundings. From the comparison of pretest and posttest, participants' ability increased sharply to encourage and improve the literacy ability of scientific papers in Indonesia.Abstract in BahasaDi tahun 2022 Mendeley meluncurkan Mendeley Reference Manager sehingga perlu dilakukan pelatihan sebagai bentuk pengabdian kepada masyarakat yang bertujuan untuk meningkatkan kemampuan literasi karya ilmiah dalam hal pencarian dan sitasi suatu pustaka. Kegiatan bermitra dengan Ngampooz sehingga bisa terorganisasi dengan baik mulai dari pendaftaran peserta hingga penyerahan materi dan sertikat peserta melalui aplikasi Ngampooz. Kegiatan utama yaitu pelatihan dilakukan secara daring dengan aplikasi Zoom dan peserta praktek secara langsung untuk setiap bagian materi di komputer masing-masing peserta. Profil peserta terdiri dari pelajar, mahasiswa, dosen, engineer, dan pegawai yang berasal dari berbagai institusi di Jakarta dan sekitarnya. Dari perbandingan pretest dan posttest, kemampuan peserta meningkat tajam sehingga bisa mendorong dan meningkatkan kemampuan literasi karya ilmiah di Indonesia.